Coexistence scheme of licensed-assisted access using long-term evolution and wireless local area network for wireless sensor networks - Woongsoo Na; Yunseong Lee; Jaehyun Eom; Sungrae Cho; Ho-Hyun Park (International Journal of Distributed Sensor Networks)
Wireless sensor networks have continuously evolved to provide better services and satisfy user demands. Through this, the number of wireless sensors and the amount of mobile traffic are exponentially growing every year. Long-term evolution technology can effectively resolve the problems caused by traffic growth; however, there are still limitations. Licensed-assisted access using long-term evolution technology has greatly improved the performance of existing long-term evolution heterogeneous networks with carrier aggregation. However, the existing wireless local area network sensor nodes remain a challenge. The licensed-assisted access using long-term evolution access point should efficiently handle the problem of monopolizing spectrum resources used by existing wireless local area network sensor nodes. In this article, we investigate an optimized time slot allocation technique for the coexistence of wireless local area network and licensed-assisted access using long-term evolution sensor nodes. In order to maximize the throughput of each wireless local area network and licensed-assisted access using long-term evolution sensor node in the proposed algorithm, we designed an objective function based on the number of wireless local area network/licensed-assisted access using long-term evolution sensor nodes and the queue size of each sensor, after which we developed the optimal parameters using Karush–Kuhn–Tucker conditions. Through extensive simulations, we show that the proposed scheme can significantly outperform the other existing techniques with respect to the throughput, channel utilization, delay, and transmission fairness.